Processos de escolarização e deficiência: trajetórias escolares singulares de ex-alunos de classe especial para deficientes mentais - Santos, Roseli Albino dos (2006)
This Doctorate's thesis thema, focuses the relationship between mental deficiency and the school processes. The objective of this study is to understand and explain, from the subject's point of view how was his school trajectory and the results reached in the school process. The study had as main theorical source the theories of Sociology iof Education, specially those who permit us to understand the student's school trajectory in the context of social relationns highlighting the study of Pierre Bourdieu and Bernard Lahire. About special education we specially relied on the studies of Bueno. In relation to the problem of stigma we highlighted the studies of Goffman. The empiric data extracted from the interviews of the 5 ex students of special classes of mental deficients were worked in a relational perspective, of the interdependence of factors. In this way, 3 big axis of analisys were constructed and in them the definition of some topics as, from meaningful aspects for the possible examination of singularity of each trajectory, being them : 1) family environmen; 2) school environment; 3) social contact. The analisys of this data revealed that even though the envolved subjects of the research attended the special the special classes for mental deficients, there are significant differences in the school processes that they lived. The school trajectories were developed in the net of the social relations lived in the family contexts, school context and in other social environments